Distributed‐hierarchical control strategy to coordinate peer‐to‐peer energy transactions and node voltages at low voltage distribution networks. Issue 6 (13th November 2020) - Fazeli, Seyed Mahdi; Li, Ran; Li, Furong
Abstract : Peer‐to‐peer (P2P) energy market has emerged as a promising way to absorb local generations. However, unregulated P2P transactions are likely to exacerbate voltage violations at distribution networks. The challenge is how to ensure P2P markets to flourish whilst maintaining system voltages within the stator limits. This study proposes a distributed‐hierarchical control structure consisting of a central controller and peer controllers to address the challenge. The central controller computes the optimised P2P transaction levels and the nodal voltage references simultaneously and sends the outcomes to the peers as routing‐update messages at regular intervals. The peer controllers are developed based on individual phase decupled P – Q theory where two individual channels follow the optimised transaction levels and nodal voltage references. The peers, also, apply a current limit strategy to release the network capacity and improve voltage profiles when confronting with short‐term voltage magnitude variations between the two update intervals. A case‐study‐based investigation shows that reactive power contributions improve the power transaction levels up to 30% while the node voltage violations are reduced. The effectiveness of the proposed strategy is validated using simulation and compared with state‐of‐the‐art voltage mitigation methodologies over the IEEE 19‐bus system.